PENGARUH PEMBERIAN AIR KELAPA MUDA TERHADAP PENURUNAN TEKANAN DARAH PADA IBU LANSIA DI WILAYAH KERJA PUSKESMAS LIMBOTO - Dewi Kaaba; Dwi Nur Octaviani Katili; Fatmah Zakaria (Akademika, 2019)
This research was conducted in the Limboto Health Center Work Area. The aim is to see whether there is an effect of giving young coconut water to the reduction in blood pressure of elderly mothers. The method used in this study is the quasi-experimental pre-posttest with the control group. The sample of this study amounted to 30 people. The data analysis used was paired simple t-test and independent t-test. The results showed the p-value of systole 0.000 and the p-value diastol 0.002 or <α 0.05 so it can be concluded that there was an effect of giving young coconut water to the reduction of blood pressure in elderly mothers. It is expected that elderly women who suffer from hypertension can use young coconut water therapy as a non-pharmacological treatment for hypertensionPenelitian ini dilakukan di Wilayah Kerja Puskesmas Limboto. Tujuannya untuk melihat apakah pengaruh pemberian air kelapa muda terhadap penurunan tekanan darah ibu lansia. Metode yang digunakan dalam penelitian ini yaitu quasi eksperimen pre-posttest dengan kelompok kontrol. Sampel penelitian ini berjumlah 30 orang. Analisis data yang digunakan adalah paired simple t-test dan independent t-test. Hasil penelitian menunjukan nilai p-value sistol 0.000 dan nilai p-value diastol 0.002 atau < α 0.05 sehingga dapat disimpulkan ada pengaruh pemberian air kelapa muda terhadap penurunan tekanan darah pada ibu lansia. Diharapkan bagi ibu lansia yang menderita hipertensi agar dapat menggunakan terapi air kelapa muda sebagai pengobatan nonfarmakologi anti hipertensi.